Transcriptional Responses of Creeping Bentgrass to 2,3-Butanediol, a Bacterial Volatile Compound (BVC) Analogue - Shi, Yi (Molecules, 2017)
Bacterial volatile compounds (BVCs) have been reported to enhance plant growth and elicit plant defenses against fungal infection and insect damage. The objective of this study was to determine transcriptomic changes in response to synthetic BVC that could be associated with plant resistance to Rhizoctonia solani in creeping bentgrass. The 2,3-butanediol (BD) (250 µM) was sprayed on creeping bentgrass leaves grown in jam jars. The result showed that synthetic BD induced plant defense against R. solani for creeping bentgrass. Transcriptomic analysis demonstrated that more genes were repressed by BD while less showed up-regulation. BD suppressed the expression of some regular stress-related genes in creeping bentgrass, such as pheromone activity, calcium channel activity, photosystem II oxygen evolving complex, and hydrolase activity, while up-regulated defense related transcription factors (TFs), such as basic helix-loop-helix (bHLH) TFs, cysteine2-cysteine2-contans-like (C2C2-CO) and no apical meristem TFs (NAC). Other genes related to disease resistance, such as jasmonic acid (JA) signaling, leucine rich repeats (LRR)-transmembrane protein kinase, pathogen-related (PR) gene 5 receptor kinase and nucleotide binding site-leucine rich repeats (NBS-LRR) domain containing plant resistance gene (R-gene) were also significantly up-regulated. These results suggest that BD may induce changes to the plant transcriptome in induced systemic resistance (ISR) pathways.